PERUBAHAN FISIOLOGIS PASCAPANEN BUAH MAHKOTA DEWA (Phaleria macrocarpa) - Iswahyudi wahyudi; D.Danar TriWinanti; Herna Permata S.; Nurul Imamah; Tri Yulni (Universitas Islam Madura, 2015)
God’s crown (Phaleria macrocarpa) is a medicinal plant of Papua. Fruit flesh which is physiologically mature is used for pharmaceutical industry. Maturity index of the fruit can be observed from bright red skin and hard texture. However, the physiological changes of the fruit has not been widely studied. The purpose of this study was to assess changes in postharvest physiology in term of color and weight loss. The fresh fruit parameters observed were harvesting time, color, and uniform in size. The fruit is washed, then stored at room temperature, and observed physiological changes every 24 hours for 21 days until the fruit is damaged. Color parameters including index L, a, b were observed using Adobe Photoshop CS6, while weight loss is measured using digital scales. Data were processed by means of Microsoft Excel 2007. The results showed that the fruit color changed from green to red within 12-15 days of storage due to degradation of chlorophyll and synthesis of carotenoids. Weight loss increased during storage because of respiration and transpiration. Additionally, the fruit quality was drastically decreased as result of decay process, which is accelerated by the presence of pathogens.